Federal government debt and economic growth: Evidence from Malaysia - Daud S.N.M.; Podivinsky J.M. (SAGE Publications Ltd, 2024)
This article conducts an investigation into the effect of federal government debt on Malaysias economic growth with the application of threshold regression. The result reveals that, beyond the government debt threshold level, the country is experiencing a positive effect on economic growth. 2015, 2015 SAGE Publications.